Role of actin in shaping autophagosomes. Issue 12 (1st December 2016) - Zientara-Rytter, Katarzyna; Subramani, Suresh
ABSTRACT: One of the main unanswered questions regarding the early steps of macroautophagy/autophagy is the mechanism of membrane-modeling events required for autophagosome formation. Three independent studies have recently revealed an actin cytoskeleton involvement in this process, providing significant details regarding the role of actin in nucleation events both inside and outside the phagophore membrane during its expansion and assembly.